PERANCANGAN MEDIA PROMOSI SANGGAR TARI RAFF DANCE COMPANY SEBAGAI UPAYA MENCIPTAKAN BRAND AWARENESS - Pahlawan P.B, Rizky Senja; Bahruddin, Muh; Yosep, Sigit Prayitno (Jurnal Art Nouveau, 2015)
Abstract: Dance studio âRaff Dance Companyâ is one of dance companies which is still active and has potential in Surabaya. Dance studio âRaff Dance Companyâ has the potential to produce high value dance in the creation of dance in Indonesia. The problem is less known by the public as another dance studio. In conducting a media campaign, so far dance studioâRaff Dance Company only carry out promotional activites in the form of banner media that is only located in the cultural park âCak Durasimâ Surabaya. Besides, other promotional media are not up to date, such as social media like Facebook and Twitter. This resulted in the information submitted by dance studio âRaff Dance Companyâ was not conveyed to the dance studioâRaff Dance Companyâ to increase the brand awareness. This problem took some effort to improve the brand awareness, one is to design a right and proper media campaign for dance studio âRaff Dance CompanyâKeywords: Design, Dance Studio, Brand Awareness